2009
DOI: 10.1016/j.ijsolstr.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear micromechanical formulation of the high fidelity generalized method of cells

Abstract: a b s t r a c tThe recent High Fidelity Generalized Method of Cells (HFGMC) micromechnical modeling framework of multiphase composites is formulated in a new form which facilitates its computational efficiency that allows an effective multiscale material-structural analysis. Towards this goal, incremental and total formulations of the governing equations are derived. A new stress update computational method is established to solve for the nonlinear material constituents along with the micromechanical equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…This micromechanics model has been reviewed by Aboudi (2004) and more recently has been shown by Haj-Ali and Aboudi (2009) to provide excellent prediction for (undamaged) nonlinear and inelastic matrix composites by extensive comparisons with finite element solutions. In addition, this micromechanics model has been coupled by these authors to a finite element software to investigate the response of metal matrix composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…This micromechanics model has been reviewed by Aboudi (2004) and more recently has been shown by Haj-Ali and Aboudi (2009) to provide excellent prediction for (undamaged) nonlinear and inelastic matrix composites by extensive comparisons with finite element solutions. In addition, this micromechanics model has been coupled by these authors to a finite element software to investigate the response of metal matrix composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Haj-Ali and Aboudi [25] formulated the HFGMC model in a new form that facilitates its computational efficiency. To this end, the explicit matrix form of the HFGMC model was presented, which allowed an immediate and convenient computer implementation of the model.…”
Section: Micromechanics Modelmentioning
confidence: 99%
“…A detailed review of this class of nonlinear micromechanical methods can be found in [1][2][3], among several others. In addition, the prediction of the local deformation process of periodic alternate multiphase materials requires the detailed description of the spacial description of the soft and hard phases subject to different kinds of loading [4]. Hence, the formation of constitutive equations that govern the large deformations of composite materials, which consist of elasto-viscoplastic phases, is necessary for the modeling and analysis of their deformation behavior.…”
Section: Introductionmentioning
confidence: 99%